DAMPAK TOXIC PARENTING TERHADAP PERKEMBANGAN EMOSIONAL REMAJA DI RT 003 RW 005 DESA SUKAJAYA KECAMATAN BOJONGPICUNG KABUPATEN CIANJUR - Septiani, Thia; Ansori, Ansori (IKIP Siliwangi, 2025)
Toxic parenting behavior is bad behavior carried out by parents which can hinder the emotional development of teenagers. Toxic Parenting occurs due to several factors. First, parents are not satisfied with the child's results. Both parents do not understand the science of parenting and the dangers of toxic parental behavior. This research uses qualitative methods with data collection using observation, documentation and interview methods. Meanwhile, data collection techniques are carried out using three methods, namely data reduction, data presentation and drawing conclusions. The results of the research show that there is an impact of toxic parenting on the emotional development of teenagers in RT 03 Sukajaya Village, Bojongpicung District, Cianjur Regency including, (1) The pressure that children feel due to behavioral actions carried out by parents (2) The potential for self-injury is quite large, such as attempting suicide due to physical violence by parents. (3) Passion for learning decreases, because they are not given access to develop their potential (4) Become a stronger and more independent person.